Beware the band adhesion: an unexpected cause of double obstruction following intraperitoneal kidney transplantation. Issue 8 (14th August 2020) - Tovmassian, David; Tang, Linda; Hameed, Ahmer M; Yao, Jinna; Yoon, Peter Daechul; Lee, Taina; Laurence, Jerome M; Yuen, Lawrence P K; Allen, Richard D M; Lau, Howard; Pleass, Henry C C
Abstract: Small bowel obstruction (SBO) following intraperitoneal renal transplantation, either solitary or due to simultaneous pancreas-kidney transplantation, is a known complication. While SBO is most commonly due to adhesions, there have been documented cases of internal herniation following simultaneous pancreas-kidney transplantation with enteric drainage due to the formation of a mesenteric defect. We present a unique complication in which the transplant ureter has caused strangulation and necrosis of a length of small intestine. The transplant ureter was mistaken for a band adhesion and divided. Post-operative anuria signalled this difficult diagnosis. Subsequent re-look laparotomy and ureteric reimplantation with Boari flap were required. Therefore, it is important to consider the ureter as a cause of internal herniation in kidney transplant patients and recognize that a band adhesion within the pelvis may in fact be the transplant ureter, obstructing a loop of small intestine beneath its course.